2022
DOI: 10.1002/chem.202201517
|View full text |Cite
|
Sign up to set email alerts
|

Azole‐Directed Cobalt‐Catalyzed Asymmetric Hydrogenation of Alkenes

Abstract: The azole‐directed cobalt‐catalyzed asymmetric hydrogenation of alkenes has been developed with high efficiency. With this approach, chiral pyrazole compounds were obtained in quantitative yields and excellent enantioselectivities (up to 99 % ee) under mild conditions, and the hydrogenation was conducted on a gram scale with up to 2000 TON. Several useful applications were demonstrated including the convenient introduction of β‐chirality to a drug intermediate containing an azole ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 122 publications
0
13
0
Order By: Relevance
“…Based on previous studies on cobalt-catalyzed asymmetric olefin hydrogenation by Chirik, our group, , and others, we found that cobalt-catalyzed asymmetric hydrogenation of 1,1-disubstituted alkenes led to a certain amount of undesired E / Z mixtures of thermodynamically more stable trisubstituted alkenes as side-products, which were quite difficult to separate from the desired hydrogenated products. Although this olefin isomerization issue limited the utility of the protocol, it does offer an opportunity to stereoconvergently convert the alkene isomers.…”
mentioning
confidence: 91%
“…Based on previous studies on cobalt-catalyzed asymmetric olefin hydrogenation by Chirik, our group, , and others, we found that cobalt-catalyzed asymmetric hydrogenation of 1,1-disubstituted alkenes led to a certain amount of undesired E / Z mixtures of thermodynamically more stable trisubstituted alkenes as side-products, which were quite difficult to separate from the desired hydrogenated products. Although this olefin isomerization issue limited the utility of the protocol, it does offer an opportunity to stereoconvergently convert the alkene isomers.…”
mentioning
confidence: 91%
“…Based on a series of differentiated cobalt catalytic systems, a wide variety of alkene substrates, bearing largely unfunctionalized groups (UFG) as well as functionalized groups (FG) including acylamino, carboxyl, and azolyl, can be hydrogenated with excellent enantioselectivities and yields (Scheme a, up). From the data recorded, bis­(phosphine) (PP) ligands are more suitable for the latter and often achieve a higher catalytic efficiency (up to 2000 TON). It is important to note that the assisted coordinating groups such as a pyrazolyl with N -coordination are critical for the high efficiency in the cobalt-catalyzed asymmetric hydrogenation of functionalized olefins, which enables the reaction to proceed smoothly at ambient temperature and pressure and to complete quickly within 1 h (Scheme a, down) …”
mentioning
confidence: 99%
“…These results coupled with our understanding of the catalytic mechanism propelled us to envisage that cobalt-catalyzed efficient asymmetric hydrogenation of the CO bond may no longer be out of reach. Compared with the traditional acyl and hydroxyl groups using the oxygen atom as the coordinating atom, the imino and amino groups using the nitrogen atom as the coordinating atom are considered to form stronger coordinate bonds . In particular, the simple primary amino group (NH 2 ) has the least steric hindrance and, thus, is more favorable for coordination bond formation.…”
mentioning
confidence: 99%
See 2 more Smart Citations